IMPLIKASI JANJI (WA'D) DALAM TRANSAKSI SYARIAH TERHADAP TRANSAKSI IJARAH MUNTAHIYA BITTAMLIK - Achmad Zaky; Luluk Farida (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2018)
The aim of this research is to describe the implications arising from the introduction of DSN-MUI Fatwa No.85/DSN-MUI/XII/2012 on Ijarah Muntahiya Bittamlik (IMBT). This study analyzes the practices of IMBT based on the guidelines which are Fatwa DSN-MUI No.27/2002 and PSAK 107, Accounting for Ijarah after aplication of DSN-MUI Fatwa No.85/DSN-MUI/XII/2012. This research is a descriptive literature study. The findings indicate that the application of the DSN-MUI Fatwa No.85/DSN-MUI/XII/ 2012 is needed by transactions using Wa’d especially IMBT because it can bring benefits, as they ensure legal certainty and the continuity of contracts. However, there is another impact of the adoption of DSN-MUI Fatwa No.85/DSN-MUI/XII/ 2012, namely IMBT has a Ta'alluq risk and potentially meet the criteria of a conditional purchase. Referring to the adoption of PSAK 107, DSN-MUI Fatwa No.85/DSN-MUI/XII/2012, it also results in the risk of Capital Lease criteria fulfillment on the akad of IMBT